Use of Compact Digital Cervicography: An Adjuvant Screening Tool for Precancerous Cervical Lesions - Zip-Pon Chen; Hong-Ming Chen; Tim-Tso Lee (Elsevier, 2008)
Objective: In an attempt to develop a new model to screen for cervical cancer, we set up a digital camera mounted with a macro lens for cervicography. This digitalized compact form of cervicography with the Reid colposcopic index (RCI) can be applied as an adjuvant tool to screen for abnormal Papanicolaou (Pap) smears. Materials and Methods: Among 21,532 cases screened with a Pap smear, we enrolled 125 cases with precancerous smears for this prospective study. An 8-megapixel Canon digital camera with a macro lens and a light source comprised the compact digital cervicographic system. The results of compact digital cervicography were reported using the RCI scoring system. Cases with high-grade squamous intraepithelial lesion or atypical glandular cells of undetermined significance were transferred to medical centers for further confirmation and management. In total, 119 cases underwent compact digital cervicography. The data were analyzed with the McNemar test. Results: With the digitized results of compact digital cervicography, we were able to show patients with precancerous Pap smears their cervix and help them understand its status. For patients with an abnormal Pap smear, the results of performing compact digital cervicography combined with the RCI scoring system were statistically significant (p < 0.05). Conclusion: The use of compact digital cervicography with the RCI scoring system is a significant device for screening abnormal Pap cases. It helps to improve patient care. Further research is required to understand the discrepancies among diagnostic results of Pap smears (the Bethesda system), cervicography with RCI, and histopathology. [Taiwan J Obstet Cynecol 2008;47(2):187-191]